Pharmaceutical Effects of Inhibiting the Soluble Epoxide Hydrolase in Canine Osteoarthritis - McReynolds, Cindy B.; Hwang, Sung Hee; Yang, Jun; Wan, Debin; Wagner, Karen; Morisseau, Christophe; Li, Dongyang; Schmidt, William K.; Hammock, Bruce D. (Frontiers in Pharmacology, 2019)
Osteoarthritis (OA) is a degenerative joint disease that causes pain and bone deterioration driven by 13 an increase in prostaglandins and inflammatory cytokines. Current treatments focus on inhibiting 14 prostaglandin production, a pro-inflammatory lipid metabolite, with NSAID drugs; however, other 15 lipid signaling targets could provide safer and more effective treatment strategies. Epoxides of 16 polyunsaturated fatty acids are anti-inflammatory lipid mediators that are rapidly metabolized by the 17 soluble epoxide hydrolase (sEH) into corresponding vicinal diols. sEH inhibitors (sEHI) stabilize 18 these biologically active, anti-inflammatory lipid epoxides and are analgesic in both neuropathic and 19 inflammatory pain conditions. Additionally, increased diols have been observed in the synovial fluid 20 of humans with OA, warranting further research on the biological role of this pathway in the 21 progression of OA. 22 Most experimental studies testing the analgesic effects of sEH inhibitors have used experimental 23 rodent models which do not completely represent the complex etiology of painful diseases. Here, we 24 tested the efficacy of sEH inhibitors in aged dogs with natural arthritis to provide a better 25 representation of the clinical manifestations of pain. Two sEHI were administered orally, once daily 26 for five days to dogs with naturally occurring arthritis to assess efficacy and pharmacokinetics. 27 Blinded technicians recorded the behavior of the arthritic dogs based on pre-determined criteria to 28 assess pain and function. After five days, EC1728 significantly reduced cumulative pain at a dose of 29 5 mg/kg compared to vehicle controls. Pharmacokinetic evaluation showed concentrations exceeding 30 the enzyme potency in both plasma and synovial fluid. In vitro data showed that epoxyeicosatrienoic 31 acid (EETs), epoxide metabolites of arachidonic acid, decreased inflammatory cytokines, IL-6 and 32 TNF-α, in canine chondrocytes challenged with IL1β to simulate an arthritic environment. These 33 results provide proof of concept that inhibiting the sEH is a non-NSAID, non-opioid strategy for 34 treating osteoarthritis.